Involvement of Prohibitin Upregulation in Abrin-Triggered Apoptosis. (25th September 2011) - Liu, Yu-Huei; Peck, Konan; Lin, Jung-Yaw
Abstract : Abrin (ABR), a protein purified from the seeds of Abrus precatorius, induces apoptosis in various types of cancer cells. However, the detailed mechanism remains largely uncharacterized. By using a cDNA microarray platform, we determined that prohibitin (PHB), a tumor suppressor protein, is significantly upregulated in ABR-triggered apoptosis. ABR-induced upregulation of PHB is mediated by the stress-activated protein kinase/c-Jun NH2-terminal kinase (SAPK/JNK) pathway, as demonstrated by chemical inhibitors. In addition, ABR significantly induced the expression of Bax as well as the activation of caspase-3 and poly(ADP-ribose) polymerase (PARP) in Jurkat T cells, whereas the reduction of PHB by specific RNA interference delayed ABR-triggered apoptosis through the proapoptotic genes examined. Moreover, our results also indicated that nuclear translocation of the PHB-p53 complex may play a role in the transcription of Bax. Collectively, our data show that PHB plays a role in ABR-induced apoptosis, which may be helpful for the development of diagnostic or therapeutic agents.